An Î©(n^[1/3]) lower bound for bilinear group based private information retrieval - Razborov, Alexander; Yekhanin, Sergey (Theory of Computing, 2007)
A two server private information retrieval (PIR) scheme allows a user U to retrieve the i-th bit of an n-bit string x replicated between two servers while each server individually learns no information about i. The main parameter of interest in a PIR scheme is its communication complexity, namely the number of bits exchanged by the user and the servers. A large amount of effort has been invested by researchers over the last decade in search for efﬁcient PIR schemes. A number of different schemes [6, 4, 19] have been proposed, however all of them ended up with the same communication complexity of O(n1/3). The best known lower bound to date is 5logn by [17]. The tremendous gap between upper and lower bounds is the focus of our paper. We show an Ω(n1/3) lower bound in a restricted model that nevertheless captures all known upper bound techniques. Our lower bound applies to bilinear group based PIR schemes. Abilinear PIR scheme is a one round PIR scheme, where user computes the dot product of servers’ responses to obtain the desired value of the i-th bit. Every linear scheme can be turned into a bilinear one with an asymptotically negligible communication overhead. A group based PIR scheme is a PIR scheme that involves servers representing database by a function on a certain ﬁnite group G, and allows user to retrieve the value of this function at any group element using the natural secret sharing scheme based on G. Our proof relies on representation theory of ﬁnite groups.